2011
DOI: 10.1002/jssc.201100197
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous monolithic supports for affinity chromatography

Abstract: In the early 1990s, three research groups simultaneously developed continuous macroporous rod-shaped polymeric systems to eliminate the problem of flow through the interparticle spaces generally presented by the chromatography columns that use particles as filler. The great advantage of those materials, forming a continuous phase rod, is to increase the mass transfer by convective transport, as the mobile phase is forced to go through all means of separation, in contrast to particulate media where the mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 86 publications
(103 reference statements)
0
28
0
Order By: Relevance
“…Molecular imprinting is a sub field of biomimetic, which is very popular recently (Wulff 1995). Currently, MIPs have been used effectively in a wide range of fields from separation sciences, purification, sensors to drug delivery and extracorporeal therapy in consequence of their unique nature (Haginaka et al 1999, Lozinsky et al 2001, Wulff 2002, Piletsky et al 2006, Li and Li 2007, Haginaka 2008, Arrua and Alvarez Igarzabal 2011. Macroporous cryogels get great attention especially in biotechnology, biomedicine and pharmaceutics.…”
Section: Introductionmentioning
confidence: 98%
“…Molecular imprinting is a sub field of biomimetic, which is very popular recently (Wulff 1995). Currently, MIPs have been used effectively in a wide range of fields from separation sciences, purification, sensors to drug delivery and extracorporeal therapy in consequence of their unique nature (Haginaka et al 1999, Lozinsky et al 2001, Wulff 2002, Piletsky et al 2006, Li and Li 2007, Haginaka 2008, Arrua and Alvarez Igarzabal 2011. Macroporous cryogels get great attention especially in biotechnology, biomedicine and pharmaceutics.…”
Section: Introductionmentioning
confidence: 98%
“…They therefore exhibit different advantages and disadvantages. A number of review articles have been published in the last decade describing progresses on their preparations, properties, and applications [12][13][14][15][16][17][18]. It can be easily found that the problems of both the swelling or shrinkage of organic monoliths in some solvents and the tedious fabrication procedures of the silica-based monoliths always encumber the researchers and limit the applications.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the stability over a wide pH range considering strong changes in pH for elution, a low nonspecific binding, and the provision of functional groups for ligand immobilization 3. Over the last few years, supports based on organic monoliths have become more popular, which is reflected in publication of several reviews dealing with various applications of monolithic supports in affinity chromatography 4–12. Most organic monoliths such as commonly used support materials based on agarose are stable over a large pH range.…”
Section: Introductionmentioning
confidence: 99%